2021
DOI: 10.1126/sciadv.abe0084
|View full text |Cite
|
Sign up to set email alerts
|

Submilligram-scale separation of near-zigzag single-chirality carbon nanotubes by temperature controlling a binary surfactant system

Abstract: Mass production of zigzag and near-zigzag single-wall carbon nanotubes (SWCNTs), whether by growth or separation, remains a challenge, which hinders the disclosure of their previously unknown property and practical applications. Here, we report a method to separate SWCNTs by chiral angle through temperature control of a binary surfactant system of sodium cholate (SC) and SDS in gel chromatography. Eleven types of single-chirality SWCNT species with chiral angle less than 20° were efficiently separated includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 61 publications
(223 reference statements)
2
51
0
Order By: Relevance
“…Separating SWCNTs in solution phase has made great progress. ,,, Many separation techniques, such as dielectrophoresis, ultracentrifugation, chromatography, gel filtration, and aqueous two-phase separation, have been developed to isolate s-SWCNTs. However, in most of the reports, only s-SWCNTs with diameters below 1 nm were sorted .…”
Section: Introductionmentioning
confidence: 99%
“…Separating SWCNTs in solution phase has made great progress. ,,, Many separation techniques, such as dielectrophoresis, ultracentrifugation, chromatography, gel filtration, and aqueous two-phase separation, have been developed to isolate s-SWCNTs. However, in most of the reports, only s-SWCNTs with diameters below 1 nm were sorted .…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, the exchange of DOC with SDS molecules on the SWCNT surface, occurs in a diameter-dependent manner, and thereby allows for a diameter-dependent separation of SWCNTs with ATP. Similar competition between another bile salt surfactant sodium cholate and SDS was studied in the references [55,56]: it was shown that at high SDS concentrations bile salt micelles are penetrated by SDS molecules, changing the SWCNT environment.…”
mentioning
confidence: 60%
“…S7 and Table S1†), which is close to the purity of (6,5) SWCNTs sorted by other reported methods. 35,37 Both the absorption and PL characterization demonstrate that nearly monochiral (6,5) SWCNTs were extracted from {PW 12 }-SWCNTs by PCz wrapping.…”
Section: Resultsmentioning
confidence: 99%
“…There has been significant progress in the solution processing based sorting of SWCNTs with controlled structures, including ultracentrifugation, 29,30 electrophoretic 31 and/or chromatographic separation, 32–35 aqueous two-phase separation, 36–41 etc. Among them, the one-pot separation of semiconducting SWCNTs by conjugated polymers is of particular interest and has become the method of choice for circuit and solar cell applications due to the simplicity, high purity, and high thin film quality.…”
Section: Introductionmentioning
confidence: 99%